Pengembangan Model Bahan Ajar Menulis Berita Berbasis Koran Linggau Pos Siswa Kelas 8 SMP Negeri Sumber Rejo - Sugi Murniasih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
The purpose of this study is to 1) design the development of learning materials for writing news-based newspaper Linggau Pos students of grade 8 of SMP Negeri Sumber Rejo, 2) Describe the news material based on Linggau Pos newspaper class 8 students of Sumber Rejo State Junior High School valid, and effective. This research and development there are 10 stages of Dick and Carey model which is limited to 8 stages. Interview data were analyzed by qualitative data analysis technique. The value of the questionnaire and the results of the assignment of students writing the news is used to determine the quantitative data. Expert team validation results show the model of teaching materials News Based Writing Newspaper Post categorized very well. Prototype trials and small group trials show the model of news writing materials based on Linggau Pos newspaper is practical. Based on large group trials there 5 students who are not complete of 28 students, while the questionnaire given to large groups showed very positive results. Instrument validity is categorized very high with percentage 0.99. thitung greater than ttable 43.659 greater than 2.052 means there is a significant positive relationship between the model of learning materials developed with learning outcomes. Instrument reliability is categorized high with a value of 0.66. The correlations test showed no significant relationship between the mean value data after and the average value before. Paired sample ttest with SPSS version 20, shows Sig value. 2 tailed of 0.0001 is smaller than the alpha value of 0.05, which means there is a significant difference between before and after using the teaching materials model of News Based Newspaper Linggau Pos. Keywords : Development, Material Model, News Writing.